2015
DOI: 10.1007/s10980-015-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Mowing succession of species composition is determined by plant growth forms, not photosynthetic pathways in Leymus chinensis grassland of Inner Mongolia

Abstract: Context Previous studies demonstrate that mowing inhibits tall species but facilitates short species and C 4 species. However, as each species has a growth-form and simultaneously a C-pathway, it is important to know whether the effects of mowing on a species is determined only or majorly by its growth-from or C-pathway. Objective We test the hypothesis that mowing facilitates the growth of short species and of C 4 species, and disentangle the interactive effects of plant growth-forms and C-pathways on plant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It is often assumed that mowing homogenizes vegetation structure (Tälle et al., ) but we found no decline in structural vegetation heterogeneity on mowed subplots (mowing reduced vegetation height, but not variation in height). Increased light availability from reduced vegetation height and biomass likely contributed to the positive effects of mowing on species diversity (Baoyin, Li, Minggagud, Bao, & Zhong, ; Skálová et al., ). Removing cut biomass after mowing reduces soil nutrient levels (Venterink, Kardel, Kotowski, Peeters, & Wassen, ) and can have positive effects on Australian grasslands that are threatened by nutrient enrichment (Verrier & Kirkpatrick, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often assumed that mowing homogenizes vegetation structure (Tälle et al., ) but we found no decline in structural vegetation heterogeneity on mowed subplots (mowing reduced vegetation height, but not variation in height). Increased light availability from reduced vegetation height and biomass likely contributed to the positive effects of mowing on species diversity (Baoyin, Li, Minggagud, Bao, & Zhong, ; Skálová et al., ). Removing cut biomass after mowing reduces soil nutrient levels (Venterink, Kardel, Kotowski, Peeters, & Wassen, ) and can have positive effects on Australian grasslands that are threatened by nutrient enrichment (Verrier & Kirkpatrick, ).…”
Section: Discussionmentioning
confidence: 99%
“…Declines in mowing and haymaking over the past century have reduced biodiversity in regions where mowing has been integral to the historical management of semi‐natural grasslands (e.g., several hundred years in Asia and over a thousand years in Europe; Baoyin et al., ; Feurdean et al., ; Koyama, Koyanagi, Akasaka, Takada, & Okabe, ; Pärtel, Helm, Reitalu, Liira, & Zobel, ). Few studies have quantified the effect of mowing on biodiversity in Australian grasslands (Fensham et al., ; Lewis et al., ; Morgan, ; Verrier & Kirkpatrick, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mowing and grazing are related but distinct ecological disturbances or land use practices. Based on monitoring data from a typical steppe over 30 years, Baoyin et al (2015) found that the species composition of mowed grasslands was determined primarily by plant growth form (e.g., annuals, perennial bunchgrasses, perennial rhizome grasses, forbs, and shrubs and semi-shrubs). This result differs from the previous finding that plant community composition in mowed grasslands was influenced mainly by plant height and photosynthetic pathways, suggesting the importance of considering plant functional diversity in grassland management.…”
Section: Human Impacts On Ecosystem Processesmentioning
confidence: 99%
“…chinensis steppe during January to July was a significant variable in simplified multiple regression analyses [ 24 ]. Baoyin et al reported that a quadratic function was a better predictor of NPP than linear or logarithmic equations [ 25 ]. Both quantity and timing of precipitation play a key role in the productivity and species richness of annual and perennial species in temperate grassland ecosystems [ 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%